River Water Consumption as A Source of Drinking Water with Caries in Stunting Children - Rasuna Ulfah; Anderi Fansurna; Meggy Wulandari Kai; Muhammad Yusril Pratama (Poltekkes Kemenkes Kupang, 2024)
Stunting is a chronic nutritional problem, which is currently still an important problem in Indonesia. Chronic malnutrition also has an impact on dental and oral health, such as causing disturbances in the development of salivary glands and can affect the eruption time of milk teeth, which can increase the risk of dental caries. The purpose of this study is to examine the impact of consuming river water as drinking water on caries in stunted children in Sungai Tuan Ilir Village, Banjar Regency. This research is an analytical survey with a cross-sectional design. The study population consisted of elementary school children from the Sungai Tuan Ilir Village area in Banjar Regency. The sampling method used was total sampling, involving 95 children. The results of the research using the Chi-Square Tests obtained a Sig value. (2-tailed) = 0.000, so there is a relationship between drinking water consumption and dental caries in stunted children. The conclusion drawn from this study is that there is a significant relationship between water consumption and caries in stunted children in Sungai Tuan Ilir Village, Banjar Regency. It is recommended that promotive and preventive efforts need to be increased from pregnant women to toddlers regarding stunting and the importance of maintaining healthy teeth as early as possible.